2013
DOI: 10.1186/1471-2482-13-s2-s35
|View full text |Cite
|
Sign up to set email alerts
|

Risk of acute myocardial infarction after transurethral resection of prostate in elderly

Abstract: BackgroundBenign prostatic hyperplasia is a frequent disease among elderly, and is responsible for considerable disability. Benign prostatic hyperplasia can be clinically significant due to lower urinary tract symptoms that take place because the gland is enlarged and obstructs urine flow. Transurethral resection of the prostate remains the gold standard treatment for patients with moderate or severe symptoms who need active treatment or who either fail or do not want medical therapy. Moreover, perioperative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 56 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…With the progressive aging of the population, the prevalance of vascular diseases is increasing ( 8 ). In their study, Lucia et al reported that TURP had low risk for severe complications, but cardiovascular events in elderly patients undergoing this surgical operation were more common than in general population ( 9 ). With an increase in the number of elderly population that requires surgical procedures and anticoagulant/ antiaggregant therapy, these patients need great concern for possible complications related to accompanied comorbidities ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the progressive aging of the population, the prevalance of vascular diseases is increasing ( 8 ). In their study, Lucia et al reported that TURP had low risk for severe complications, but cardiovascular events in elderly patients undergoing this surgical operation were more common than in general population ( 9 ). With an increase in the number of elderly population that requires surgical procedures and anticoagulant/ antiaggregant therapy, these patients need great concern for possible complications related to accompanied comorbidities ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, women tend to be older than men at diagnosis and exhibits a different phenotype: the HF with preserved ejection fraction (HFpEF) is more frequent in women and new onset of HF with reduced ejection fraction (HFrEF) in men [10]. Moreover, despite women with present HF at an older age, where comorbidities are more frequent, some studies showed that women have a lower cardiovascular and all-cause mortality [11,12], suggesting that the phenotypic differences in HF presentation and prognosis between women and men may be the consequence of progressive, sex-specific changes in cardiac and vascular physiology. Furthermore, the menopausal transition may influence the development of cardiovascular risk factors in women [13].…”
Section: Sex-gender and Hfmentioning
confidence: 99%
“…Transurethral resection prostate (TURP) is a gold standard surgery to overcome the problems of prostate gland enlargement (El-Hakim, 2010;De Lucia et al, 2013). TURP can be performed by considering certain clinical manifestations including post-void residual volume, recurrent haematuria and urinary retention, acute kidney failure and urolithiasis (Chamber, 2002;Rassweiler et al, 2006).…”
Section: Introductionmentioning
confidence: 99%